Zakat as an Instrument of Economic Redistribution: Perspectives of Islamic Law and Indonesian Positive Law - Purwanti Purwanti; Nur Arifudin (Dinasti International Journal of Digital Business Management, 2026)
This comprehensive research delves into the crucial role of zakat as a mechanism of economic redistribution, by examining fundamentally its theoretical foundations and practical implementation through two main lenses: Islamic Law and Indonesian Positive Law. This research is motivated by the ongoing challenges of economic inequality in Indonesia, a Muslim-majority country, and seeks to explore how zakat, which is a pillar of Islamic economics, can be optimized as a formal instrument of fiscal and social policy within a modern national legal framework. Within the framework of Indonesian Positive Law, this study documents a significant legal transformation. The ratification of Law Number 23 of 2011 concerning the Management of Zakat represents a formal "positivization" of this Islamic norm into the national legal system. This law institutionalizes zakat through the establishment of the National Amil Zakat Agency (BAZNAS) and the licensed Amil Zakat Institution (LAZ), transforming it from a voluntary religious practice to a state-regulated and institutionalized instrument for public policy. This shift expands the purpose of zakat to be in line with national development goals, including poverty alleviation, improving community welfare, and supporting the Sustainable Development Goals (SDGs). Using normative legal research methods equipped with conceptual, legislative, and comparative approaches, this study identifies the gap between a robust legal framework and the reality on the ground. The main challenges that weaken the effectiveness of zakat include low compliance from prospective payers (muzakki), the dominance of short-term consumptive assistance compared to long-term productive empowerment, weak integration of data and digital systems, lack of transparency in several management bodies, and incomplete synergistic relationships with the national tax system. In response to this challenge, the research formulated a multi-faceted strategic framework for strengthening zakat. The recommendations proposed are: (1) Regulatory reform, including revising Law No. 23/2011 to clarify the role of BAZNAS and LAZ and strengthen the position of zakat as a tax deductor; (2) Institutional Transformation, which focuses on improving the professionalism, accountability, and digital capacity of zakat (amil) managers; (3) Optimization of Productive Zakat, by advocating for a paradigm shift towards programs that empower recipients (mustahik) through micro business financing, training, and mentoring to achieve economic independence; (4) Systemic Synergy, by encouraging the integration of zakat into government poverty alleviation programs and the broader Islamic social finance ecosystem; and (5) Public Education and Literacy to increase awareness and trust in formal zakat institutions. In conclusion, this study confirms that zakat has great potential as an alternative religious-based fiscal instrument in the Indonesian legal system. Its unique dual identity—as a religious obligation and a tool of state policy—provides a solid foundation for overcoming economic disparities. However, realizing this potential depends on the implementation of holistic structural reforms, which successfully integrate the enduring values of Islamic law with the demands of modern, transparent, and effective governance